Mobile Banking Application Accounting Information System (For Bank Syariah Indonesia Employees In Bandung City At KC Bandung Suniaraja Branch, KC Bandung Asia Afrika, KC Bandung Citarum, KC Bandung Astana Anyar And KCP Bandung Dago) - Inta Budi Setya Nusa; Siti Rohmah Nurhayati (SEAN Institute, 2024)
Accounting Information System Mobile Banking Applications have become a part of the daily lives of many individuals and businesses in today's digital era. This study aims to examine the level of security and ease of use of this system, as well as its impact on user satisfaction. This study used a qualitative approach to collect data through questionnaires. The results show that the level of security has a significant role in shaping user satisfaction of accounting information system mobile banking applications. Some respondents consider that this system provides an adequate level of security in protecting their data and financial transactions. However, some concerns still exist related to potential security risks, such as account ans identity theft. In addition, ease of use also has a big impact on user satisfaction. The easy to use and intuitive system makes users more satisfied and likely to use mobile banking apps regularly. Factors such as simple navigation, user friendly interface, and good integration with other features also contribute to higher levels of satisfaction. Security and user convenience are two key aspects that are interrelated and should be seriously considered to create a successful mobile banking application accounting information system that satisfies users.